Herida por arma de fuego con lesión pulmonar, del plexo braquial, arteria axilar e intercostal - Brito Sosa, Germán; Iraizoz Barrios, Ana María (My University, 2021)
Introduction: Chest traumas with associated vascular lesions worsen the prognosis of patients due to hemorrhage. 80 % of all vascular traumas affect the extremities and 30 % are located in the upper limbs. Being able to use the patient's own tissues for repair is a viable treatment alternative, and sometimes the only possible one. Objective: To present a patient with chest trauma with vascular lesions, where the saphenous vein was used to restore the damage in the axillary artery and the tractotomy technique for massive hemothorax with lesion of the lung parenchyma. Clinical case: 32-year-old male patient with a gunshot wound to the shoulder and right hemithorax, which caused injury to the right axillary artery and massive hemothorax. A thoracotomy with tractotomy was performed at the level of the right upper lobe and ligation of the intercostal artery; and the right axillary region was explored to repair vascular damage. Conclusions: To treat penetrating chest trauma with bleeding lung injury, a pulmonary tractotomy and hemostasis should be performed to avoid intraparenchymal hematomas. Faced with an irreparable axillary artery injury, the saphenous vein is a viable alternative for its restoration and to achieve the vitality of the limb.
Introducción: Los traumas de tórax con lesiones vasculares asociadas, empeoran el pronóstico de los pacientes debido a la hemorragia. El 80 % de todos los traumas vasculares afectan las extremidades y el 30 % se localizan en los miembros superiores. Poder utilizar los propios tejidos del paciente para su reparación, es una alternativa de tratamiento viable, y en ocasiones la única posible. Objetivo: Presentar un paciente con trauma de tórax, con lesiones vasculares, en quien se utilizó la vena safena para restaurar el daño en la arteria axilar y la técnica de tractotomía, por hemotórax masivo con lesión del parénquima pulmonar. Caso clínico: Paciente masculino de 32 años, con herida causada por arma de fuego a nivel del hombro y hemitórax derecho, que ocasionó lesión de arteria axilar derecha y hemotórax masivo. Se realizó toracotomía con tractotomía a nivel del lóbulo superior derecho y ligadura de la arteria intercostal; y se exploró la región axilar derecha para reparar el daño vascular. Conclusiones: Para tratar el traumatismo torácico penetrante con lesión pulmonar sangrante, se debe realizar una tractotomía pulmonar y hemostasia, para evitar los hematomas intraparenquimatosos. Ante una lesión de arteria axilar irreparable, la vena safena es una alternativa viable para su restauración y lograr la vitalidad de la extremidad
Keywords: ARTERIA AXILAR; HEMONEUMOTORAX; PLEXO BRAQUIAL; VENA SAFENA; LESION PULMONAR